Students’ and lecturers’ experiences of digitally transformed Open Distance Learning at higher education level - Teane, F. M. (South African Journal of Higher Education, 2024)
The outbreak of the Covid-19 pandemic and subsequent lock-down restrictions forced higher education institutions to move towards a fully online mode of delivery. The study explored the teaching and learning experiences of both students and lecturers within such a digitally transformed higher education space. Concerns have however been raised about this sudden move towards the fourth industrial revolution due to the levels of readiness of higher education institutions. A qualitative research approach was followed, and I purposeful selected ten masters’ course work students and two lecturers. One-on-one interviews and a focus group discussion were utilised for data generation. The Saldana’s thematic method was employed to analyse data. The findings of my research point to both positive and negative experiences of students and lecturers, following the shift to online teaching and learning. Negative experiences highlight the need for support systems to be put in place in a digitally transformed educational milieu.